Meningitis, meningococcal meningitis and MenB: an explainer for community nurses. - Devine, Elaine (Journal of Community Nursing)
Meningitis is uncommon, but it remains one of the infections that community nurses need to keep front of mind because deterioration can be rapid and the consequences devastating. This article explains what meningitis is, why meningococcal meningitis and meningococcal B disease matter in UK practice, how symptoms may present across age groups, and what community nurses can do to support early recognition, urgent escalation, vaccination uptake and recovery.